A influência do tipo e do fracionamento dos alimentos nas sensações de saciação e saciedade do consumidor - Stocker, Leticia Rocha (2016)
Consumer behavior towards food is full of paradoxes and complex decisions, often involving seemingly irreconcilable tradeoffs (WERLE AND CUNY, 2012). One such tradeoff involves the nature of the food to be consumed, whether it is hedonic or utilitarian. Another tradeoff involves portion sizes and, interestingly, how it is presented (whole or fractioned) and consumed. While some studies found no difference in consumption intake between people eating a single size portion compared to a fractionated portion (DEVITT AND MATTES, 2004 AND SPIEGEL ET AL., 1993), other studies show that, by consuming food through little pieces, people tend to consume less (MARCHIORI, WAROQUIER AND KLEIN, 2011). Unit size of food and types of food influence consumption in ways that go beyond the quantity consumed. They can influence perceptions of hunger and fullness. While the sensation of termination of hunger can be described in physiological terms, like the absence of pain in the stomach, the sensation of fullness is often described through a more psychological perspective. In this sense, fullness is related to the pleasure people can feel through the consumption of food (MURRAY AND VICKERS, 2009). Even though types and unit size of food have already been addressed on their own rights, the joint consideration of these two aspects has not yet been explored. Our research addresses this issue. Specifically, we test whether people fell less hunger or feel more fullness through the consumption of hedonic vs. utilitarian food, and through single sized (whole) portions vs. fractionated portions of food. Given the nature of our constructs, we also believe such effects can be influenced by an individual’s capacity to self-regulate. Hence, we considered self-control as a moderating variable. Our findings advance the knowledge on food consumption by arguing that hedonic foods are more pleasurable than utilitarian foods, and that utilitarian foods have more power to cease hunger than hedonic foods. More interestingly, these effects are influenced by both unit size (whether food is presented whole or in pieces) and individual levels of self-control. Individuals with low self-control take greater advantage of the fullness properties of hedonic and hunger-ceasing properties of utilitarian foods when they are presented whole. Such results have direct implications for public policy.